EFEITO DA SUBSTÂNCIA APAZIGUADORA BOVINA (SAB) SOBRE A PERFORMANCE À IATF E DESEMPENHO PRODUTIVO DE NOVILHAS NELORE - MACHADO, João Victor Bezerra; DA SILVA, Aldair Félix; CORDEIRO, Dauydison Antônio Gonzales; DA SILVA, Millena Vitória; STERZA, Fabiana de Andrade Melo; SOUZA, Andréa Roberto Duarte Lopes (ANAIS DO ENIC, 2024)
-